2020
DOI: 10.7554/elife.53479
|View full text |Cite
|
Sign up to set email alerts
|

A CLC-ec1 mutant reveals global conformational change and suggests a unifying mechanism for the CLC Cl–/H+ transport cycle

Abstract: Among coupled exchangers, CLCs uniquely catalyze the exchange of oppositely charged ions (Cl– for H+). Transport-cycle models to describe and explain this unusual mechanism have been proposed based on known CLC structures. While the proposed models harmonize with many experimental findings, gaps and inconsistencies in our understanding have remained. One limitation has been that global conformational change – which occurs in all conventional transporter mechanisms – has not been observed in any high-resolution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 113 publications
(196 reference statements)
1
61
0
Order By: Relevance
“…In addition, the structure involves a rearrangement of the three glutamine residues: Gluex (Glnex), the H + -transfer residue, reaches inwards for H + exchange to the intracellular side, while the intracellular Gln residues separate from one another, allowing for a water/H + pathway from the intracellular side ( Figure 1B). The relevance of this conformation to the wild-type (WT) protein was confirmed using double electron-electron resonance (DEER) spectroscopy experiments to compare conformations of WT and QQQ mutant proteins; these experiments revealed that wild-type CLC-ec1 adopts a QQQ-like conformation when the pH is lowered from 7.5 to 4.5 to protonate the key glutamate residues (Chavan et al, 2020).…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…In addition, the structure involves a rearrangement of the three glutamine residues: Gluex (Glnex), the H + -transfer residue, reaches inwards for H + exchange to the intracellular side, while the intracellular Gln residues separate from one another, allowing for a water/H + pathway from the intracellular side ( Figure 1B). The relevance of this conformation to the wild-type (WT) protein was confirmed using double electron-electron resonance (DEER) spectroscopy experiments to compare conformations of WT and QQQ mutant proteins; these experiments revealed that wild-type CLC-ec1 adopts a QQQ-like conformation when the pH is lowered from 7.5 to 4.5 to protonate the key glutamate residues (Chavan et al, 2020).…”
Section: Introductionmentioning
confidence: 95%
“…Mutagenesis experiments to generate the E377C/H234C, Y75C/H234C, and Y75C/E377C mutants were carried out in a cysteine-less background (C85A/C302A/C347S) (Nguitragool and Miller, 2007), in either an otherwise WT CLC-ec1 background or in a "QQQ" background (E148Q/E203Q/E113Q) (Chavan et al, 2020). Mutants were verified by sequencing the entire coding region of the gene.…”
Section: Protein Overexpression and Purificationmentioning
confidence: 99%
See 3 more Smart Citations